Student Solutions Manual and Study Guide for Serway and Jewett's : Physics for Scientists and Engineers (Vol. I) - Gordon, John R. ; McGrew, Ralph V. and Serway, Raymond A. (Southbank., Australia Thomson, Brooks/Cole, 2008)
For Chapters 23-46, this manual contains detailed solutions to approximately 20% of the problems per chapter (indicated in the textbook with boxed problem numbers). The manual also features a skills section, important notes from key sections of the text, and a list of important equations and concepts
Include Picture
Keywords: Physics